Analysis of Soybean Availability in Indonesia - Grace Natalia; Dwidjono Hadi Darwanto; Slamet Hartono (Jurnal Ilmu Pertanian, 2017)
This study aimed to determine the factors affected the soybean availability in Indonesia. This study used secondary data obtained from FAO (Food and Agriculture Organization), World Bank, and the Ministry of Finance. In this study, the data from 1964 to 2013 used to determine the factors affected soybean availability in Indonesia . The Error Correction Model (ECM) was used to determine the factors affected soybean availability. The results showed that (1) the data were stationary at first difference; (2) the data used co-integrated means long-term parameters; (3) ECT coefficient was 0.846 (significant at α = 5%) indicated the model used was valid. Soybean availability in Indonesia in the short term was positively influenced by the total planted area, total soybean consumption, and soybean import tariffs. In the long term, soybean availability in Indonesia was positively influenced by the total planted area, productivity of soybean, domestic soybean prices, soybean consumption, and rupiah exchange rate to dollar. In the long-term, availability of soybeans was negatively affected by the price of imported soybean.